Multiculturalism or Assimilation? Refugees and Immigrants as Europeans - Bujalska, Katarzyna (E- Revista de Estudos Interculturais, 2021)
Recent years have been characterized by the emergence of a large migration flow in the European Union (EU), which is mainly due to the emergence of an armed civil conflict in Syria, the expansion of the self-proclaimed Islamic State and the spread of conflicts in Syria. For this reason, thousands of immigrants want to reach Europe via the Mediterranean Sea or the Balkans. In fact, migratory movements have existed since very old times and are proceeding with the process of human evolution. Migratory movements are most often caused by economic, social, cultural, political or environmental issues. This new wave of refugees has posed a number of political, economic, social and cultural challenges in European countries. Therefore, the EU has been seeking a common position to maximize the effectiveness of the refugee reception policy. This has not been possible due to the position of some states who reject the distribution program of refugees over the European continent. In this context, the Convention on the status of crises (Geneva Convention of 1951) is very important, as it provides a legal framework for the regulation of refugees’ concepts and issues. The aim of this work is to discuss the legal regulations for refugees and immigrant’s political situation, as well as their integration and assimilation process in different countries. This article analyses the European case, with a special emphasis on the specific situation of Portugal and Poland, concerning the issue of refugees and how integration processes work. This choice was made due to the fact that there is no common policy for the integration of refugees in Europe, and as long as the measures of each country are in compliance with international law, different policies can be adopted.